2021
DOI: 10.3389/fnins.2021.737874
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for Cognitive Decline in Chronic Pain: A Systematic Review and Meta-Analysis

Abstract: Background: People with chronic pain (CP) sometimes report impaired cognitive function, including a deficit of attention, memory, executive planning, and information processing. However, the association between CP and cognitive decline was still not clear. Our study aimed to assess the association of CP as a risk factor with cognitive decline among adults.Methods: We included data from clinical studies. Publications were identified using a systematic search strategy from PubMed, Embase, and Cochrane Library da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 64 publications
1
18
0
Order By: Relevance
“…1A), as memory impairment, foggy brain and problems with attention, are recognized consequences of depressive and/or anxious states 37 and chronic pain. 38 The impact of baseline characteristics, including age and CFS, and the persistence of long-COVID-19 on HR-QoL, was also investigated. Righi et al 21 reported that a status of excellent physical health, present in 90% of patients prior to SARS-CoV-2 infection declined to 24% at disease onset and then increased to 82% at nine-months of follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…1A), as memory impairment, foggy brain and problems with attention, are recognized consequences of depressive and/or anxious states 37 and chronic pain. 38 The impact of baseline characteristics, including age and CFS, and the persistence of long-COVID-19 on HR-QoL, was also investigated. Righi et al 21 reported that a status of excellent physical health, present in 90% of patients prior to SARS-CoV-2 infection declined to 24% at disease onset and then increased to 82% at nine-months of follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…These results are in line with two recent meta-analyses, which failed to show a clear association between chronic pain and cognitive decline and advocated for further investigations. 5,6 Our findings are strengthened in that we adjusted for important confounders known to influence cognitive function, such as APOE ε4 carrier status, depressive symptoms, and intake of analgesics. 47 Moreover, our outcomes consisted of composite scores of memory and executive function, validated in ADNI, a well-established cohort specifically designed to investigate questions pertaining to AD.…”
Section: Discussionmentioning
confidence: 68%
“…Large longitudinal studies suggest that chronic pain is associated with cognitive decline and incident dementia 3,4 . However, two recent systematic reviews and meta‐analyses failed to show an unequivocal link between the two conditions, highlighting the heterogeneity among the included studies in terms of pain definition and assessment, follow‐up time, neuropsychological testing, and definitions of cognitive decline and dementia 5,6 . Furthermore, analyses were not always adjusted for risk factors known to alter cognitive function such as analgesic intake and depression, highly prevalent in chronic pain 7 .…”
mentioning
confidence: 99%
“…11 Another factor associated with cognitive impairment is chronic pain conditions, where problems with concentration, memory, processing and attention are prevalent. 12,13 A common cause of chronic pain is peripheral neuropathic pain, a condition that has shown changes in the neural pathways involved in cognition. 9,14 Peripheral neuropathic pain is experienced by 15-25% of individuals with diabetes and DPN in their lower extremities and is known as painful DPN.…”
Section: Introductionmentioning
confidence: 99%